(untitled) - LeVeque, Randall J. (Cambridge, 2002)
This book contains an introduction to hyperbolic partial differential equations and a powerful class of numerical methods for approximating their solution, including both linear problems and nonlinear conservation laws. These equations describe a wide range of wave propagation and transport phenomena arising in nearly every scientific and engineering discipline. Several applications are described in a self-contained manner, along with much of the mathematical theory of hyperbolic problems. The methods studied are implemented in the CLAWPACK software package and source code for all the examples presented can be found on the web, along with animations of many of the simulations. This provides an excellent learning environment for understanding wave propagation phenomena and finite volume methods.
Keywords: Differential equations, Hyperbolic,Finite volume method,Conservation laws (Mathematics),Phương trình vi phân, Hyperbolic,Phương pháp khối lượng hữu hạn,Bảo tồn pháp luật (Toán học); Numerical solutions,Giải pháp Numerical